The Existence of a Halal Product Assurance Organizing Body in Organizing Halal Assurance - Farid Wajdi (International Journal Reglement & Society (IJRS), 2021)
The problem has not been applied to the principles of sustainability, justice, legal certainty, accountability,  openness, effectiveness and efficiency, and professionalism must all be considered  in  providing guarantees of Halal Products. Theimplementation of Halal Product Guarantee aims to provide comfort, security, security, and certainty of the availability of Halal Products for the general public when consuming and using products, as well as increasing added value for Businesses that produce and sell Halal Products. The government is responsible for organizing halal product guarantees, implemented by BPJPH, to provide  excellent service to the  public. The research method used in this research is normative juridical. The results showed that the philosophy of bpjph was formed to carry out the implementation of halal product guarantees, so that BPJPH is responsible to the Minister of Religious Affairs. Comparison with the United States, Malaysia, and Thailand that  LPH in america is held through a private organization or legal entity that does not have the slightest affiliation with the government. Generally there are several institutions / organizations that issue halal certificates (HalalCertifier Bodies)in acountry. LPH in Malaysia is a Halal Axis Division under the Malaysian Department of Islamic Progress (JAKIM). JAKIM is an official government body  and its performance follows the rules of the Government of Malaysia. LPH in Thailand is  the Central Islamic Committee of Thailand  (CICOT) and the Islamic Committee of Province.